Training of teachers who teach Mathematics with DICT in the Elementary School: a systematic review of the SBEM publications - Silva, Judith Ferreira da; Queirós, Wellington Pereira de (Educação Matemática Debate, 2024)
This bibliographic survey identifies teachers training models that address the teachers training for assignments in mathematics in the Elementary School with DICT. We use, as a theoretical foundation, the training models of José Contreras, and the documentary research methodology of the chronicle type. We have investigated a total of ten articles which were published between 2013 and 2022, in the SBEM journals, and in articles from the ENEM annals. The analysis showed the implicit predominance of the reflective training model for teachers. Thus, we point out the need for research that theoretically explains the training models being used and that addresses the use of DICT from the perspective of the critical intellectual model of mathematics teachers training.